2023
DOI: 10.1109/tbme.2023.3252368
|View full text |Cite
|
Sign up to set email alerts
|

MSED: A Multi-Modal Sleep Event Detection Model for Clinical Sleep Analysis

Abstract: Clinical sleep analysis require manual analysis of sleep patterns for correct diagnosis of sleep disorders. However, several studies have shown significant variability in manual scoring of clinically relevant discrete sleep events, such as arousals, leg movements, and sleep disordered breathing (apneas and hypopneas). We investigated whether an automatic method could be used for event detection and if a model trained on all events (joint model) performed better than corresponding event-specific models (single-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…These should be mixed to reduce individual scorer bias. Other studies have shown that combining different micro-events during sleep improves results 21 . Therefore, we aim to further improve the results by adding other micro-events during sleep and sleep staging.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…These should be mixed to reduce individual scorer bias. Other studies have shown that combining different micro-events during sleep improves results 21 . Therefore, we aim to further improve the results by adding other micro-events during sleep and sleep staging.…”
Section: Discussionmentioning
confidence: 97%
“…They improved this approach in 2020 20 by using different setups for their EEG channels, and achieved similar results on the test set with only a third of the training data. This approach was later extended by Zahid et al 21 by combining arousal detection with leg movement and sleep-disordered breathing, presumably using the same test set of 1000 male participants. They also included the correlation between the calculated ArI and the manually scored ArI in their evaluation.…”
Section: Related Workmentioning
confidence: 99%